Metabolic power, volatile compounds, and flavor marker formation mechanisms of three fungi isolated from Fengxiangxing Daqu - Cao, Dan; Lv, Jiali; Liu, Cui; Jin, Chengyong; Zhang, Yongli; Zhang, Yuhang; Zhang, Wen (Frontiers in Microbiology, 2025)
IntroductionChinese Daqu is a naturally formed microbial complex, which is the fermenter of Chinese Baijiu. The microorganisms in Chinese Daqu determine the flavor of Chinese Baijiu.MethodsBased on PacBio SMRT ITS sequencing technology, fungal genome de novo sequencing, and Headspace Solid-Phase Micro-extraction/Gas Chromatography-Mass Spectrometry analyzed and identified three fungi, their abundance, volatile compounds, and flavor markers in Daqu.ResultsAspergillus chevalieri, Saccharomycopsis fibuligera, and Thermoascus aurantiacus were the three most abundant fungi, with relative abundances of 5.702, 31.686, and 62.256%, respectively. Aspergillus chevalieri and Saccharomycopsis fibuligera were associated with volatile markers of chained terpene alcohols and lactones, with linalool and γ-nonanolactone identified as their flavor markers, respectively. Thermoascus aurantiacus produced the highest variety and content of pyrazine. According to the functional annotation and metabolic relationship of the whole genomes of Aspergillus chevalieri and Saccharomycopsis fibuligera in COG, KEGG and other databases, the formation mechanism and possible metabolic pathways of linalool and γ-nonanolactone were elucidated. The results of the study revealed the different contributions of the three dominant fungi to the volatile compounds of Daqu, can provide ideas for the study of the contribution of other microorganisms to the volatile compounds of Daqu and the mechanism. It can provide a basis for the precise adjustment of the flavor of Daqu, and then the precise modification of the flavor of Baijiu.